Teacher Assessments in Colombia (2018-2024): A Critical Documentary Analysis - Valcárcel Quezada , Dario (2026)
This study comprises a documentary analysis of teacher performance evaluation in Colombia between 2018 and 2024, with the aim of identifying its main strengths, weaknesses, opportunities, and threats. The study responds to the need to understand the tensions among existing regulatory frameworks, teachers’ perceptions, and the structural conditions that affect educational quality. To this end, a qualitative, exploratory approach was adopted, based on a systematic review of 50 documents selected through predefined inclusion and exclusion criteria. The corpus included laws, decrees, circulars, institutional technical reports, and indexed scientific articles, located through the SciELO, Google Scholar, and Redalyc databases. Content analysis was organized using the SWOT method as a strategy to classify information across key dimensions: type of institution, geographic area, and educational level. The findings reveal significant regulatory advances, such as the implementation of digital platforms and standardized protocols in urban areas. However, structural challenges persist that limit the impact of these advances, including the punitive perception of evaluations, the disconnect between results and formative incentives, and regional inequalities that hinder equitable implementation. The study concludes that the teacher evaluation system requires a transformation that promotes professional development, pedagogical support, and territorial equity. The absence of empirical triangulation is also acknowledged as a limitation, and future research is recommended to incorporate teachers’ voices and official statistical data. This work constitutes an initial critical approach intended to contribute to the debate on more inclusive and context-sensitive educational policies.